Pengaruh Motivasi Intrinsik, Kepuasan Kerja, dan Kedisplinan dalam bekerja Terhadap Komitmen Organisasi pada Karyawan Cv. Mitra Tehknik - Setioko, Herman; Septyarini, Epsilandri; Purnamarini, Tri Ratna (Universitas Hamzanwadi, 2024)
Employees are one of the important elements a company has. This research was conducted to analyze the influence of intrinsic motivation, job satisfaction, and discipline at work on organizational loyalty in CV Mitra Tehknik employees. In this research, quantitative methods were used, data collection was carried out through distributing questionnaires using hard files. The population in this study were employees of CV Mitra Teknik located in Semin, Gunungkidul. The sample in this study amounted to 57 respondents. The data analysis method uses descriptive analysis and multiple linear regression. This research produces: (1) loyalty to the organization is not influenced by intrinsic motivation, this can be seen from the calculated value of the intrinsic motivation variable, namely 0.686 with a relevant level of 0.496 > 0.05; (2) there is a negative impact on job satisfaction and is not relevant to organizational commitment, this can be seen from the t-calculated value of the job satisfaction variable -1.193 with a relevant level of 0.238 > 0.05; (3) there is a negative and irrelevant impact on organizational loyalty, this can be seen from the calculated value of the discipline variable at work -1.238 > 0.05; (4) there is a positive and relevant impact on work motivation on organizational loyalty, this can be seen from the t-count value of the work motivation variable -1.193 with a relevant level of 0.238 > 0.05; (5) there is a positive impact on job satisfaction and is relevant to organizational loyalty, this can be seen from the tcount value of 05; (3) discipline at work has a positive and relevant impact on organizational loyalty, as evidenced by the t value of 2.958 with a relevance level of 0.004 < 0.05; (4) intrinsic motivation, job satisfaction, and discipline at work simultaneously have a positive and relevant impact on organizational loyalty, as evidenced by the fcount value of 6.169 with a relevance level of 0.001 < 0.05